Countering Public Opposition to Immigration: The Impact of Information Campaigns - Giovanni Facchini; Yotam Margalit; Hiroyuki Nakata (Institute of Labor Economics (IZA), 2016)
Popular sentiment toward immigration is often antagonistic, making the integration of migrants one of the most important yet daunting challenges facing societies in advanced economies. Can information campaigns decrease public opposition to immigration? This paper reports results from a large-scale experiment conducted in Japan, a country with widespread anti-immigration sentiment. Embedded in a comprehension study, we randomly exposed a large national sample of citizens to information pertaining to potential social and economic benefits from immigration. Depending on the treatment, we find that this exposure led to a substantial increase in support for a more open immigration policy. The treatments also motivated citizens to take political action in support of this cause. Notably, while smaller in magnitude, many effects also persisted 10-12 days after the treatment. The results highlight the potential value of combating enmity to incoming foreigners with campaigns that inform the public about key positive impacts of immigration.
Keywords: F12; F16; L11; 330; immigration; information campaigns; experiment; public opinion; Japan